Leaf morphology explains the disparity between annual bluegrass and creeping bentgrass growth under foliar fertilization. (16th March 2018) - O'Connor, Kelly; Hébert, François; Powers, Jacqueline E.; Jordan, Katerina S.; Lyons, Eric Michael
ABSTRACT: On golf courses planted to creeping bentgrass, invasion of annual bluegrass is a constant concern. To analyze if nitrogen fertilization manipulation could bias growth to creeping bentgrass, both grasses were fertilized either through foliar or soil application with either urea or ammonium sulfate and the impact on shoot and root growth measured. Ammonium sulfate resulted in greater overall growth for both species. Foliar application resulted in greater shoot growth for annual bluegrass and soil application resulted in greater root growth for creeping bentgrass. Leaf samples, as well as multiple leaf samples collected from golf courses, were examined microscopically for potential routes for foliar nutrient uptake: stomata and aqueous pores. No statistical difference was observed in the stomatal number between the two species but annual bluegrass possessed more aqueous pores. The enhanced ability of annual bluegrass to benefit from foliar fertilization may aid in its encroachment on highly managed golf greens.